2012
DOI: 10.1128/aem.07661-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bioaerosols from Dairy Barns: Reconstructing the Puzzle of Occupational Respiratory Diseases by Using Molecular Approaches

Abstract: ABSTRACTTo understand the etiology of exposure-related diseases and to establish standards for reducing the risks associated with working in contaminated environments, the exact nature of the bioaerosol components must be defined. Molecular biology tools were used to evaluate airborne bacterial and, for the first time, archaeal content of dairy barns. Three air samplers were tested in each of the 13 barns sampled. Up to 106archaeal and 108 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 35 publications
(48 reference statements)
9
54
1
2
Order By: Relevance
“…We obtained similar results, confirming that the two methods are comparable (data not shown). The same observation was previously published by our team (39).…”
Section: Methodssupporting
confidence: 84%
“…We obtained similar results, confirming that the two methods are comparable (data not shown). The same observation was previously published by our team (39).…”
Section: Methodssupporting
confidence: 84%
“…The concentrations obtained for the NTC were subtracted from each series. The chosen protocol for bioaerosols quantification has been used in different type of environments with no inhibition observed …”
Section: Methodsmentioning
confidence: 99%
“…There is a direct link between organic dust-related microbial exposures such as: inhalation of gram negative and gram positive bacteria; microbial components -- lipopolysaccharide, peptidoglycans [6], fungal beta glucans [32*]; and lung disease in CAFO workers. Bioaerosol characterization studies demonstrated that microbial agents present in barn dust can deposit in the lungs of farmers and their family members [33,34]. Agricultural bioaerosols also contain fungal 1,3-ÎČ-glucan, particles in the respirable range (1 ÎŒm diameter), which can deposit deep within the lungs and cause respiratory illness [32*].…”
Section: Diversity and Factors Affecting Agricultural Environment Expmentioning
confidence: 99%